A supercapacitor based on cement-based electrode and preparation method thereof
By doping steel fibers into cement-based supercapacitors and oriented arrangement using magnetic field, combined with nano super-dispersed water-absorbing resin, the capacitance reduction problem caused by the increase in electrode thickness is solved, the power storage capacity and mechanical properties are improved, and large-volume application is achieved. Dual function of engineering structural materials.
Patent Information
- Application Number
- CN202410640598.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The existing cement-based supercapacitors have too thin electrodes that cause the capacitance to drop. When the thickness exceeds 1 cm, the specific capacitance declines sharply, and the strength of the cement base after adding carbon powder decreases, limiting the large-volume application of cement base as a structural material.
By doping steel fibers and induced directional arrangement of steel fibers with magnetic fields, combined with nano super-dispersed water-absorbing resin, the power storage capacity and mechanical properties of cement-based supercapacitors are improved.
The electrode thickness of cement-based supercapacitors has been significantly improved, the storage performance is maintained without attenuation, the bending strength is increased by 800%, and the fracture energy is increased by 20 times, which has promoted the dual functions of large-scale power storage equipment and the engineering structural materials.
Smart Images

Figure CN118398390B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitors, and in particular to a supercapacitor based on cement-based electrodes and a preparation method thereof. Background Art
[0002] Traditional power systems usually rely on stable power generation sources to meet continuous energy demand. However, with the increase of renewable energy, power systems need more flexibility and adaptability to regulate and balance the grid when energy supply and demand are unbalanced. The storage of intermittent energy such as wind and solar energy has always attracted much attention. The problem of developing large-scale and efficient energy storage equipment needs to be solved urgently. Carbon cement supercapacitors use cement as the matrix and nano-carbon black with a large specific surface area. The reservoir formed by cement hydration pores realizes a high-power density supercapacitor based on physical storage of electrons. This is one of the effective ways to solve large-scale energy storage problems in the future.
[0003] At present, cement-based supercapacitors are all supercapacitors with cement-based materials as electrolytes, and there are no supercapacitors with cement-based materials as electrodes. There is a clear difference between cement-based materials as electrolytes and electrodes: the former is to fill the cement-based material with salt solution to make electrolytes, providing ions that can be adsorbed by the double electric layer of the electrode. Because the conductivity of cement-based materials is not very high, there is no need for insulating diaphragms. In fact, the effect of using saturated cement-based materials as electrolytes is much worse than putting them directly into salt solutions, resulting in very poor capacitance. The original intention of these technologies is to use the load-bearing characteristics of cement to enable capacitors to have load-bearing capabilities; the latter is to directly use cement-based materials as electrodes, but the conductivity and specific surface area of cement-based materials need to be further greatly improved, and an insulating diaphragm needs to be added in the middle of the cement electrode. In terms of performance, the capacitance is several orders of magnitude higher than the former, and it also has the advantage of load-bearing, and it is simple to prepare, and it itself serves as a dual function of current collector and electrolyte.
[0004] There are very few existing technologies for preparing supercapacitors using cement-based materials as electrodes. Only one paper published last year (Carbon-cement supercapacitors as a scalable bulk energy storage solution) proposed a new solution for storing electrical energy in cement - a carbon-cement supercapacitor based on cheap and easily available cement, water and carbon black. This supercapacitor has the disadvantage of too thin electrodes. The electrode thickness is preferably 0.25 cm. As the thickness increases, the specific capacitance decreases. When the electrode thickness exceeds 1 cm, the specific capacitance declines sharply. In addition, the strength of the cement-based material after adding carbon powder decreases seriously. Under the premise of ensuring the storage performance, its strength cannot even reach 5MPa for road use. This loses the meaning of using cement-based materials as electrodes to make supercapacitors, limiting the advantage of cement-based materials as structural materials that can be used in large volumes. Summary of the invention
[0005] The present invention achieves significant improvement in the storage capacity and mechanical properties of cement-based supercapacitors by adding steel fibers, inducing the directional arrangement of the steel fibers through a magnetic field, and adding nano-superdispersed water-absorbing resin.
[0006] One of the objects of the present invention is to provide a supercapacitor based on cement-based electrodes.
[0007] A second object of the present invention is to provide a method for preparing the supercapacitor based on cement-based electrodes.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a supercapacitor based on a cement-based electrode, comprising a cement-based electrode impregnated with an electrolyte, wherein the cement-based electrode is prepared by the following method:
[0010] The conductive carbon black, cement and steel fiber are mixed and stirred to obtain a dry mixture;
[0011] The water-absorbing resin monomer, the cross-linking agent, the initiator, the catalyst and the water reducing agent are added into water, mixed and stirred with the dry mixture at a certain water-cement ratio to obtain a cement-based paste;
[0012] The cement-based slurry is poured into the mold of the pre-buried conductor and then placed in the CNC coil magnetic field generating system, and the arrangement direction of the steel fibers is adjusted to be perpendicular to the cement-based electrode plane;
[0013] After the cement-based slurry is formed, it is cured and cut to obtain the cement-based electrode.
[0014] Preferably, the conductive carbon black is one or more selected from acetylene black, SP, and Ketjen black, and the specific surface area of the conductive carbon black is 50 m2 / g-1200m 2 / g;
[0015] Preferably, the cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement. The cement strength grade may be 425, 625, 325, 525, etc., without particular limitation;
[0016] Preferably, the steel fibers are straight and have a length of ≤5 mm.
[0017] In some embodiments, the mass of the conductive carbon black accounts for 8% to 13% of the mass of the cement;
[0018] In some embodiments, the mass of the steel fiber accounts for 5% to 30% of the mass of the cement.
[0019] Preferably, the water-absorbing resin monomer is one or more selected from vinyl alcohol, acrylic acid, and acrylamide monomers;
[0020] Preferably, the cross-linking agent is N,N-methylenebisacrylamide;
[0021] Preferably, the initiator is azobisisobutyronitrile;
[0022] Preferably, the catalyst is N,N,N'N'-tetramethylethylenediamine;
[0023] In some embodiments, the mass of the water-absorbing resin monomer accounts for 0.1% to 0.5% of the mass of the cement;
[0024] In some embodiments, the weight of the crosslinking agent accounts for 0.1-1% of the weight of the water-absorbing resin monomer; the weight of the initiator accounts for 0.1-1% of the weight of the water-absorbing resin monomer; and the weight of the catalyst accounts for 0.1-1% of the weight of the water-absorbing resin monomer.
[0025] Nano-scale super-dispersed water-absorbent resins can be synthesized in situ in cement-based systems. Polyvinyl alcohols (rich in hydroxyl groups), polyacrylic acids (rich in carboxyl groups), and polyacrylamides (rich in ammonium groups) can be selected. The synthesis process is to polymerize water-absorbent resin monomer molecules, cross-linking agents, initiators, and catalysts in situ in the cement-based system to achieve nanoscale dispersion of the water-absorbent resin in cement-based materials.
[0026] Preferably, the water reducer is a naphthalene-based high-efficiency water reducer.
[0027] In some embodiments, the water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2% to 0.4% of the mass of water.
[0028] In some embodiments, the digitally controlled coil magnetic field generating system is composed of a coil (for generating a magnetic field), a power supply (for powering an electromagnet), a Gauss meter (including a probe) (for measuring the magnetic field currently generated by the electromagnet as control feedback), and a computer (for controlling the size of the generated magnetic field).
[0029] In some embodiments, the curing temperature is 20±2° C., and the relative humidity is controlled at above 95%.
[0030] In some embodiments, the cement-based electrode is obtained by cutting into thin slices with a thickness of 1-20 mm and polishing on one side.
[0031] In some embodiments, the cement-based electrode based supercapacitor further comprises a glass fiber membrane.
[0032] The cement-based electrodes serve as the positive electrode and the negative electrode of the capacitor, and a glass fiber membrane is provided between the positive electrode and the negative electrode.
[0033] In a second aspect, the present invention provides a method for preparing the above-mentioned supercapacitor based on cement-based electrodes, comprising the following steps:
[0034] (1) mixing and stirring conductive carbon black, cement, and steel fiber to obtain a dry mixture;
[0035] (2) adding a water-absorbing resin monomer, a cross-linking agent, an initiator, a catalyst and a water reducing agent into water, mixing and stirring with the dry mixture at a certain water-cement ratio to obtain a cement-based slurry;
[0036] (3) pouring the cement-based slurry into the mold of the pre-buried conductor and placing it in the CNC coil magnetic field generating system, and adjusting the arrangement direction of the steel fibers to be perpendicular to the cement-based electrode plane;
[0037] (4) After the cement-based slurry is formed, it is cured and cut to obtain a cement-based electrode;
[0038] (5) The cement-based electrode is immersed in an electrolyte until saturated, combined with a glass fiber membrane, and encapsulated to obtain a supercapacitor based on a cement-based electrode.
[0039] In some embodiments, in step (1), the mass of conductive carbon black accounts for 8% to 13% of the mass of cement; the mass of steel fiber accounts for 5% to 30% of the mass of cement; and the mixing time is 20-30 minutes.
[0040] In some embodiments, in step (2), the mass of the water-absorbing resin monomer accounts for 0.1% to 0.5% of the mass of the cement; the mass of the cross-linking agent accounts for 0.1% to 1% of the mass of the water-absorbing resin monomer; the mass of the initiator accounts for 0.1% to 1% of the mass of the water-absorbing resin monomer; and the mass of the catalyst accounts for 0.1% to 1% of the mass of the water-absorbing resin monomer.
[0041] In some embodiments, in step (2), the water-cement ratio is 0.8-1.6, the mass of the water reducer accounts for 0.2% to 0.4% of the mass of water, and the stirring time is 20-25 min.
[0042] In some embodiments, in step (4), the curing temperature is 20±2° C. and the relative humidity is controlled at above 95%.
[0043] In some embodiments, in step (4), the cement-based electrode is obtained by cutting into thin slices with a thickness of 1-20 mm and polishing on one side.
[0044] In some embodiments, in step (5), the electrolyte is 1M potassium chloride solution; the thickness of the glass fiber membrane is 0.1-0.5 mm; and a packaging device is used to apply prestress to the assembled capacitor to make it fit tightly.
[0045] The mechanism of the present invention is briefly described below:
[0046] (1) Directional induction of steel fiber arrangement: prevents the carbon particle island effect and solves the problem of reduced conductivity as the thickness of cement-based electrode plates increases. Through magnetic field induction, the steel fibers are oriented perpendicular to the direction of the electrode plate, which can connect isolated carbon particles and play a role similar to the roots of a large tree, greatly increasing the depth (thickness) of the electrode's power storage effect;
[0047] (2) The role of super absorbent resin: to create "ion drainage channels" and overcome the problem of reduced ion transmission efficiency as the thickness of cement-based electrode plates increases. Super absorbent resin is a cross-linked polymer compound that absorbs water dozens to thousands of times its own weight. It can be likened to an "internal water reservoir". By selecting super absorbent resin functional groups, such as hydroxyl groups (polyvinyl alcohols are rich in hydroxyl groups) and carboxyl groups (polyacrylic acids are rich in carboxyl groups), it can form hydrogen bonds with the surface of carbon black particles, such as amino groups (polyacrylamide is rich in amino groups), forming ionic bonds with negatively charged oxygen-containing functional groups on the surface of carbon black particles, so that super absorbent resin is adsorbed near carbon black particles, forming "ion drainage channels" for carbon black particles to adsorb ions, improving the efficiency of double electric layer formation on the surface of carbon black particles, and solving the problem of low ion transmission efficiency of over-thick electrode materials.
[0048] Beneficial Effects
[0049] Under the premise of maintaining comparable power storage performance (no attenuation of specific capacitance), the present invention increases the electrode thickness by >10 times, which promotes the large-scale preparation of cement-based supercapacitors. In addition, the introduction of steel fibers increases the bending strength by >800% year-on-year and the fracture energy by >20 times. This makes it possible to become a large-scale power storage device, and also enables it to have the dual role of engineering structural materials.
[0050] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 A schematic diagram of a supercapacitor of the present invention is shown;
[0052] Figure 2 The CV curve of the sample of Example 1 at a scanning rate of 120 mV / s is shown;
[0053] Figure 3 The test piece of Example 1 is shown in 5 mA / cm 2 GCD curves at scan rates.
[0054] Illustration: 1- positive electrode (cement-based electrode); 2- glass fiber membrane; 3- negative electrode (cement-based electrode); 4- embedded conductor. DETAILED DESCRIPTION
[0055] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0056] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0057] Electrical performance test method of supercapacitor:
[0058] The electrical performance tests mainly include cyclic voltammetry test (CV) and constant current charge and discharge test (GCD).
[0059] The electrochemical performance test was carried out using the electrochemical workstation of the School of Civil Engineering and Architecture of Shandong University of Science and Technology. The electrode sheet and the diaphragm were immersed in potassium chloride electrolyte for at least 12 hours before the test. The starting voltage of the cyclic voltammetry method was 0V; the maximum voltage was 1V; the minimum voltage was 0V; the stop voltage was 0.01V; and the number of scanning cycles was 10.
[0060] Step size: 0.01V; cut-off potential of constant current charge-discharge method: 1V; charging time: 10s; acquisition interval: 0.01. The scan rates of the voltammetry test were 120mV / s, 250mV / s and 500mV / s respectively, and the current density of the cross-current charge-discharge method was 30A / cm 2 , 50A / cm 2 , the number of charge and discharge cycles is 10 times.
[0061] Capacitance: Calculated by voltammetry.
[0062] Bending strength: Passed the three-point bending test test (GB / T50081-2002).
[0063] The materials and equipment used in the embodiments are as follows:
[0064] Ketchen Black was purchased from Xinghua Kaizheng New Energy Materials Co., Ltd., with a specific surface area of 1132m 2 / g;
[0065] Steel fibers were purchased from Jiangxi Ganzhou Daye Metal Fiber Co., Ltd., with a diameter of 0.2 mm and a length of ≤5 mm;
[0066] Acrylamide, acrylic acid, N,N-methylenebisacrylamide, azobisisobutyronitrile, and N,N,N'N'-tetramethylethylenediamine were purchased from Shanghai Aladdin;
[0067] Naphthalene-based high-efficiency water reducer was purchased from Jiangsu Subote New Materials Co., Ltd., model: -B;
[0068] The CNC coil magnetic field generating system was purchased from Beijing Cuihai.
[0069] Example 1
[0070] A supercapacitor based on cement-based electrodes, the specific steps are as follows:
[0071] 1.2 g of Ketjen black, 9.6 g of 425# Portland cement, and 0.9 g of 5 mm long steel fiber were taken at a Ketjen black / cement mass ratio of 12.5%, and the mixture was stirred for 20 min to obtain a dry mixture;
[0072] 1.6 water-cement ratio, add water to the dry mixture, 0.048g of acrylamide, N,N-methylenebisacrylamide, azobisisobutyronitrile, N,N,N'N'-tetramethylethylenediamine are dissolved in the water, and the amount of each is 1% of the mass of acrylamide, and then add naphthalene-based high-efficiency water reducer, the mass of the water reducer accounts for 0.2% of the mass of water, stir for 20 minutes, pour into a 2cm*2cm*3cm mold, and place a copper wire at the bottom of the mold in advance to achieve the purpose of pre-embedding;
[0073] The mold filled with slurry is placed in the coil of the CNC coil magnetic field generating system. A one-dimensional magnetic field is used. By rotating the direction of the coil, the magnetic field direction is set to be perpendicular to the 2cm*2cm plane direction of the cement-based electrode. While the magnetic field treatment is being carried out, the mold filled with slurry is vibrated for 3 minutes on a small vibration table.
[0074] After hardening, demould and place in a curing box with a temperature of 20±2℃ and a relative humidity of more than 95% for at least 28 days;
[0075] After curing, the upper volume of the sample is cut off and the lower part is retained. The sample size after cutting is 2cm*2cm*1.5cm. Single-sided polishing is used after cutting to remove impurities in the pores using ultrasonic cleaning.
[0076] Soak the cut electrode sheets in 1M potassium chloride solution for 12 hours. Figure 1 The structure is combined with a 0.3 mm thick glass fiber membrane soaked in electrolyte to form a supercapacitor, which is then packaged in a specific container to test the electrochemical performance.
[0077] The electrochemical test cyclic voltammetry test diagram and constant current charge and discharge test diagram are as follows: Figure 2 and Figure 3 As shown. Figure 2 From the cyclic voltammetry test, it can be seen that when the scan rate is 120mV / s, the cyclic voltammetry curve is a typical shuttle shape, and the slope of the curve is large when just charging and reversing. This shows that the supercapacitor can react quickly when charging and discharging, and is suitable for applications that require fast charging and discharging. It has good reversibility, and the full shuttle shape indicates that the capacitance is considerable, making it an ideal capacitor. Figure 3 The constant current charge and discharge test shows that at a current density of 5mA / cm 2 When the charge and discharge curves are linear, it shows that it has good capacitance characteristics.
[0078] Example 2
[0079] The difference between this embodiment and embodiment 1 is that the size of the cut electrode sheet is 2 cm*2 cm*0.5 cm.
[0080] Example 3
[0081] The difference between this embodiment and embodiment 1 is that the size of the cut electrode sheet is 2cm*2cm*2cm.
[0082] Example 4
[0083] The difference between this embodiment and embodiment 1 is that the water-absorbing resin monomer is replaced with an acrylic acid monomer.
[0084] Comparative Example 1
[0085] The preparation process is basically the same as that of Example 1, except that no steel fiber and polyacrylamide are added.
[0086] Comparative Example 2
[0087] The preparation process is basically the same as that of Example 1, except that no polyacrylamide is added.
[0088] Comparative Example 3
[0089] The preparation process is basically the same as that of Example 1, except that no steel fiber is added.
[0090] Comparative Example 4
[0091] The preparation process is basically the same as that of Example 1, except that no steel fiber arrangement adjustment is performed.
[0092] The capacitance and bending strength results of the embodiments and comparative examples are shown in the following table.
[0093] Test piece Capacitance(F) Electrode thickness (mm) Bending strength(MPa) Example 1 2.00 15 2.4 Example 2 0.67 5 -- Example 3 2.55 20 -- Example 4 1.87 15 -- Comparative Example 1 0.25 15 0.3 Comparative Example 2 0.42 15 3.3 Comparative Example 3 0.36 15 0.2 Comparative Example 4 0.76 15 3.0
[0094] By comparing Example 1 with Comparative Examples 1-4, it can be concluded that the coordinated use of steel fiber orientation and super absorbent resin greatly improves the storage performance (capacitance) of cement-based supercapacitors, and exerts a synergistic effect of "1+1>2". At the same time, the addition of steel fiber also brings about a significant improvement in bending strength.
[0095] By comparing Example 1 with Examples 2 and 3, it can be concluded that as the thickness of the electrode plate increases, the capacitance also increases almost proportionally, indicating that after being treated by the method of the present invention, the increase in the thickness of the electrode plate leads to a very small decline in the storage efficiency.
[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A supercapacitor based on cement-based electrodes, characterized in that: The invention comprises a cement-based electrode soaked in an electrolyte, wherein the cement-based electrode is prepared by the following method: The conductive carbon black, cement and steel fiber are mixed and stirred to obtain a dry mixture; The water-absorbing resin monomer, the cross-linking agent, the initiator, the catalyst and the water reducing agent are added into water, mixed and stirred with the dry mixture at a certain water-cement ratio to obtain a cement-based paste; The cement-based slurry is poured into the mold of the pre-buried conductor and then placed in the CNC coil magnetic field generating system, and the arrangement direction of the steel fibers is adjusted to be perpendicular to the cement-based electrode plane; After the cement-based slurry is formed, it is cured and cut to obtain the cement-based electrode.
2. The supercapacitor based on cement-based electrodes according to claim 1, characterized in that: The conductive carbon black is one or more selected from acetylene black, SP, and Ketjen black, and the specific surface area of the conductive carbon black is 50m 2 / g-1200m 2 / g; The cement is one or more selected from the group consisting of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, fly ash silicate cement, composite silicate cement, medium heat silicate cement, low heat slag silicate cement, and white silicate cement; The steel fiber is straight and its length is ≤5mm.
3. The supercapacitor based on cement-based electrodes according to claim 1, characterized in that: The mass of conductive carbon black accounts for 8% to 13% of the mass of cement; The mass of steel fiber accounts for 5% to 30% of the mass of cement.
4. The supercapacitor based on cement-based electrodes according to claim 1, characterized in that: The water-absorbing resin monomer is one or more selected from vinyl alcohol, acrylic acid, and acrylamide monomers; The cross-linking agent was N,N-methylenebisacrylamide; The initiator is azobisisobutyronitrile; The catalyst is N,N,N'N'-tetramethylethylenediamine.
5. The supercapacitor based on cement-based electrodes according to claim 1, characterized in that: The mass of water-absorbing resin monomer accounts for 0.1% to 0.5% of the mass of cement; The weight of the crosslinking agent accounts for 0.1-1% of the weight of the water-absorbing resin monomer; the weight of the initiator accounts for 0.1-1% of the weight of the water-absorbing resin monomer; and the weight of the catalyst accounts for 0.1-1% of the weight of the water-absorbing resin monomer.
6. The supercapacitor based on cement-based electrodes according to claim 1, characterized in that: The water reducer is a naphthalene-based high-efficiency water reducer; The water-cement ratio is 0.8-1.6, and the mass of the water reducer accounts for 0.2% to 0.4% of the water mass.
7. The supercapacitor based on cement-based electrodes according to claim 1, characterized in that: The curing temperature is 20±2℃ and the relative humidity is controlled above 95%.
8. A method for preparing a supercapacitor based on cement-based electrodes according to any one of claims 1 to 7, characterized in that: The steps include: (1) mixing and stirring conductive carbon black, cement, and steel fiber to obtain a dry mixture; (2) adding a water-absorbing resin monomer, a cross-linking agent, an initiator, a catalyst and a water reducing agent into water, mixing and stirring with the dry mixture at a certain water-cement ratio to obtain a cement-based slurry; (3) pouring the cement-based slurry into the mold of the pre-buried conductor and placing it in the CNC coil magnetic field generating system, and adjusting the arrangement direction of the steel fibers to be perpendicular to the cement-based electrode plane; (4) After the cement-based slurry is formed, it is cured and cut to obtain a cement-based electrode; (5) The cement-based electrode is immersed in an electrolyte until saturated, combined with a glass fiber membrane, and encapsulated to obtain a supercapacitor based on a cement-based electrode.
9. The preparation method according to claim 8, characterized in that: In step (1), the mass of the conductive carbon black accounts for 8% to 13% of the mass of the cement; the mass of the steel fiber accounts for 5% to 30% of the mass of the cement; and the mixing time is 20-30 minutes; In step (2), the mass of the water-absorbing resin monomer accounts for 0.1% to 0.5% of the mass of the cement; the mass of the cross-linking agent accounts for 0.1% to 1% of the mass of the water-absorbing resin monomer; the mass of the initiator accounts for 0.1% to 1% of the mass of the water-absorbing resin monomer; and the mass of the catalyst accounts for 0.1% to 1% of the mass of the water-absorbing resin monomer; In step (2), the water-cement ratio is 0.8-1.6, the mass of the water reducer accounts for 0.2% to 0.4% of the mass of water, and the stirring time is 20-25 minutes.
10. The preparation method according to claim 8, characterized in that: In step (4), the curing temperature is 20±2°C and the relative humidity is controlled at above 95%; In step (4), the thin slices are cut into a thickness of 1-20 mm and polished on one side to obtain a cement-based electrode; In step (5), the electrolyte is a 1M potassium chloride solution; The thickness of the glass fiber membrane is 0.1-0.5mm.
Citation Information
Patent Citations
Graphene-cement-based high-thermal-conductivity composite material and preparation method thereof
CN106587847A
Concrete material capable of charging, storing and discharging and preparation method thereof
CN113860816A